Communal Feast Slametan: ‎ Belief System, Ritual, and the Ideal of Javanese Society - Ahmad Hakam (Universitas Negeri Jakarta, 2017)
This paper focuses on the Javanese Muslims religious belief and its ritual, slametan, ‎which is prevalently performed in Java. This ritual is of great significance to the ‎Javanese Muslim community, and is counted as syncretistic ritual of Islamic and the ‎Javanese traditions. The ritual is though analysed in relation to the society ideal of unity ‎and harmony as the standard set for the indicator that the life of people is in order and ‎in a slamet condition or ‘nothing happens’. This paper argues that this ceremony is the ‎main ritual among Javanese Muslims which to a large extent reflects and symbolises the ‎religious belief, slamet principle of the people living together, and having strong ‎awareness of others. This ideal in the end conceives some element of sacredness which ‎has the influence on the relationship between individual and social behaviour.‎